Creating a platform for costless personalization in clothing - Greenstein, Shane (Frontiers in Research Metrics and Analytics, 2022)
This study analyzes the role of co-invention in the creation of a platform for print-on-demand-clothing, or PODC. Co-invention is the invention of a new business process to complement new technology, and turn it into a valuable commercial service. PODC copies a design onto clothing with immaterial effect on the cost, and irrespective of the scale of the batch. In its modern form, PODC extends to more than two dozen different pieces of clothing and other items, enabling buyers to personalize clothing with any art. The digital printing machines used in PODC contain numerous technical inventions, while the electronic commerce platform contains the important business processes. The study examines a pioneering PODC platform from Threadless, and analyzes how this new platform emerged from a sequence of co-inventions. The study highlights the level of discretion given to graphic artists to foster trust with the platform, and it shows how a hierarchy of business process co-inventions overcame the coordination issues inherent in building a large scale and new multi-sided platform.